Strategi Pemilikian Jaringan Bisnis yang Luas di Masa Muda pada Kegiatan Pendampingan UMKM melalui Bank Mini FEBI UIN SMH BANTEN - Aan Ansori; Sofiatur Rokhmah; Nihayatul Masykuroh; Hendrieta Ferieka; Asep Dadan Suganda (Banque Syar'i : Jurnal llmiah Perbankan Syariah, 2022)
One of the ways to improve the community's economy for the campus community, especially students, as the members of mentoring activities conduct annually is entrepreneurship training and mentoring in usaha mikro kecil menengah (UMKM) activities. To the extent of increasing capabilities, seizing business opportunities, and developing their potential to become successors of business incubators who participate and take roles actively in MSME development, the Islamic Economic and Business Faculty supports economic creativity by developing various initiatives and empowerment of MSME actors. During mentoring, facilitators and business actors must analyze the stages strategically. And there are several factors for the success of business assistance, such as; 1). Broad accessibility with a companion owned, 2). The sincerity of business actors, 3). Business climate conditions that are thoroughly supportive online. And The Mini Bank FEBI, as a funder for campus entrepreneurs, finance campus community entrepreneurs, with a profit-sharing financing scheme and sharia provisions that have been set by the campus and faculty under sharia economics and sharia banking, as well as practice land of campus entrepreneurs who are in college, or who have graduated from college, supports Entrepreneurship training and mentoring in usaha mikro kecil menengah (UMKM) activities